A conceptual process for copper extraction from chalcopyrite in alkaline glycinate solutions. (July 2017) - Eksteen, J.J.; Oraby, E.A.; Tanda, B.C.
Highlights: A process is proposed for the extraction of Cu from chalcopyrite with alkaline glycine. The leach conditions are at pH > 10 at atmospheric pressure and the reagents are recycled. Cu leaching is evaluated under ambient and elevated temperatures. Cu recovery is by sulfide precipitation or solvent extraction. Cu extraction of 92% from chalcopyrite achieved in 17 h at atmospheric pressure. Abstract: A conceptual flowsheet is proposed and the main processing steps are evaluated for the alkaline processing of chalcopyrite where glycine is the complexing agent. Glycine is utilised in an oxidising, alkaline environment to leach chalcopyrite at atmospheric pressure and mildly elevated temperatures. Process steps to recover copper and glycine from alkaline aqueous solutions were also investigated. The leaching of chalcopyrite flotation concentrate in glycine solutions was conducted at different leach conditions in a 1.25 L leach reactor with an agitated slurry and controlled dissolved oxygen (DO) concentration. In the presence of air, oxygen or hydrogen peroxide or a mixture thereof, glycine can dissolve copper from chalcopyrite at either ambient or elevated (40–60 °C) temperatures and atmospheric pressure. Increasing temperature, pH, glycine concentration and DO concentration all increase the rate and extent of copper extraction. The extraction of copper from "as-received" chalcopyrite flotation concentrate, at a particle size of 100% −45 μm, in solutions containing 0.4 M glycine at 60 °C with 25 ppm DO, was 40.1% after 24 h. If the chalcopyrite concentrate underwent an ultrafine grind to100% −10 μm with prior alkaline atmospheric pre-oxidation, 92% of the copper is leached within 17 h at 60 °C, atmospheric pressure and 9% solids during a batch leach. Pyrite associated with the chalcopyrite remained unreacted during leaching of chalcopyrite and iron concentration in the final pregnant solution was found to be less than 20 mg/L. Copper recovery by sulfide precipitation from the leach solution as pure covelite was up to 99.1% at a Cu:S 2− molar ratio of 1:1. Solvent extraction (SX) experiments with LIX 84-I demonstrated that copper can be extracted into the organic phase up to 99.4% in a single stage at an equilibrium pH range 8.8–10.0. It is shown that copper can be stripped from the organic phase in a single stage acidic strip using conventional acidic return electrolyte containing 180 g/L sulfuric acid. During copper recovery by precipitation as sulfide, or by solvent extraction, the glycine is made available for recycling and reuse as a barren leach solution, after treatment with lime.